Silicon carbide-cobalt heat-conducting filler, heat-conducting PET composite material and preparation method of heat-conducting PET composite material

By preparing silicon carbide-cobalt thermal conductivity fillers, the problem of insufficient thermal conductivity of existing PET composite materials has been solved, and the thermal conductivity of PET composite materials has been significantly improved, making it suitable for fields with high thermal conductivity requirements.

CN119798793APending Publication Date: 2025-04-11HEFEI GENIUS NEW MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411954127.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The thermal conductivity of existing PET composite materials is insufficient and cannot meet the thermal conductivity needs of high-tech fields such as microelectronic packaging, high-performance thermal management systems, LED lighting and battery packs and thermal management systems of new energy vehicles.

Method used

By preparing silicon carbide-cobalt-type thermally conductive filler, amino silicon carbide is obtained by ball milling of SiC and urea, and Co2+ is adsorbed and reduced by chelation between Co2+ and amino groups, and it is fixed on the surface of amino silicon carbide to form a thermally conductive filler. The filler forms a bridge structure between SiC particles through cobalt atoms, enhancing the heat conduction efficiency.

Benefits of technology

It significantly improves the thermal conductivity of PET composite materials, allowing them to meet high thermal conductivity requirements in fields such as automobiles and home appliances, with excellent application prospects.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a silicon carbide-cobalt heat-conducting filler, a heat-conducting PET (polyethylene terephthalate) composite material and a preparation method thereof, and the preparation method of the silicon carbide-cobalt heat-conducting filler comprises the following steps: adding silicon carbide and urea into an organic solvent, mixing, carrying out ball milling to obtain a mixture, filtering, washing and drying the mixture to obtain modified silicon carbide of which the surface is modified with amino; and adding the modified silicon carbide, sodium hypophosphite and cobalt nitrate into an alkaline solution, carrying out water bath reaction, filtering, washing and drying to obtain the silicon carbide-cobalt heat-conducting filler. According to the prepared heat-conducting filler, cobalt is loaded on the surface of amino silicon carbide, the overall stability of the filler is enhanced, effective transfer of heat among SiC particles is promoted, and the heat-conducting property of the heat-conducting filler can be remarkably improved by adding the heat-conducting filler into PET.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, and in particular to a silicon carbide-cobalt thermal conductive filler, a thermal conductive PET composite material and a preparation method thereof. Background Art

[0002] Polyethylene terephthalate (hereinafter referred to as PET) is a widely used polymer resin. PET has the advantages of good fatigue resistance, good heat resistance, excellent dimensional stability, etc. However, in some specific application fields, PET has higher thermal conductivity requirements. Ordinary PET materials can no longer meet this requirement, which limits the application of PET composite materials in some specific fields.

[0003] Polyethylene terephthalate (PET) is a thermoplastic polyester material that has become one of the most widely used polymer resins in the world. PET has excellent properties: first, fatigue resistance, which allows it to maintain structural integrity under long-term stress and is not easily deformed or broken; second, heat resistance, which allows PET materials to maintain stable performance under certain high temperature environments and is not easy to melt or deform; third, dimensional stability, PET products can maintain precise size and shape during processing and use, which is particularly important for the manufacture of precision parts. These characteristics make PET widely used in packaging materials (such as beverage bottles, food containers), fiber manufacturing (such as polyester fiber clothing), electronic and electrical components, as well as construction and automotive industries.

[0004] However, with the further development of technology, the requirements for material performance are becoming increasingly stringent. Especially in some high-tech fields, such as microelectronic packaging, high-efficiency thermal management systems, LED lighting, and battery packs and thermal management systems for new energy vehicles, the thermal conductivity of materials has become one of the key factors determining product performance. In these applications, fast and effective heat conduction can not only improve the operating efficiency of the system, but also effectively prevent equipment damage or safety hazards caused by overheating. Therefore, the thermal conductivity of PET can no longer meet the needs of these high-end applications and needs to be modified. Summary of the invention

[0005] In view of this, the present invention provides a silicon carbide-cobalt-based thermally conductive filler, a thermally conductive PET composite material and a preparation method thereof to solve the problems raised in the above-mentioned background technology and to address the problem that the existing PET composite material has insufficient thermal conductivity.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] The first object of the present invention is to provide a method for preparing a silicon carbide-cobalt thermal conductive filler, which comprises the following steps:

[0008] (1) adding silicon carbide and urea to an organic solvent, mixing them, and then ball milling the mixture to obtain a mixture, filtering, washing, and drying the mixture to obtain modified silicon carbide with amino groups on its surface;

[0009] (2) Adding modified silicon carbide, sodium hypophosphite and cobalt nitrate into an alkaline solution, reacting in a water bath, filtering, washing and drying to obtain a silicon carbide-cobalt thermal conductive filler.

[0010] In a further embodiment, in step (1), the mass ratio of silicon carbide to urea is (30-40): (20-24).

[0011] In a further embodiment, in step (1), the organic solvent is an aqueous solution of isopropanol, ethanol, propanol, acetone or dimethylformamide;

[0012] In step (2), the alkaline solution is composed of a base and an organic solvent, wherein the base is sodium hydroxide or potassium hydroxide, and the organic solvent is an aqueous solution of ethanol, isopropanol or glycerol.

[0013] In a further embodiment, in step (1), the ball milling speed is 200-280 r / min and the time is 10-12 h.

[0014] In a further embodiment, in step (2), the mass ratio of the modified silicon carbide, sodium hypophosphite and cobalt nitrate is (30-40): (10-12): (26-30).

[0015] In a further embodiment, in step (2), the water bath reaction is carried out at a temperature of 50-60° C. and for a time of 8-14 h.

[0016] The second object of the present invention is to provide a silicon carbide-cobalt based thermally conductive filler prepared by the above preparation method.

[0017] The third invention object of the present invention is to provide a thermally conductive PET composite material, which is prepared by the following components in parts by weight:

[0018] PET 84-104 parts

[0019] Thermally conductive filler 10-16 parts

[0020] Antioxidant 0.1-0.5 parts

[0021] The thermally conductive filler is the above-mentioned silicon carbide-cobalt thermally conductive filler.

[0022] In a further embodiment, the antioxidant is at least one of antioxidant 168, antioxidant 1010, and antioxidant 1330.

[0023] The fourth invention object of the present invention is to provide a method for preparing the above-mentioned thermally conductive PET composite material, which comprises the following steps: weighing PET, thermally conductive filler, and antioxidant according to weight parts, mixing and stirring evenly to obtain a mixture; then adding the mixture into a twin-screw extruder, extruding and granulating to obtain the thermally conductive PET composite material.

[0024] The twin-screw extruder comprises six temperature zones arranged in sequence, wherein the temperature of zone one is 240-260°C, the temperature of zone two is 280-300°C, the temperature of zone three is 280-300°C, the temperature of zone four is 280-300°C, the temperature of zone five is 280-300°C, the temperature of zone six is ​​280-300°C, the temperature of the die head is 280-300°C, and the screw speed is 200-280r / min.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] The present invention obtains amino silicon carbide by ball milling SiC and urea, and then uses Co 2+ The amino silicon carbide adsorbs Co by chelating with amino groups. 2+ ; Then use the reducing agent sodium hypophosphite to 2+ Reduced to cobalt atoms and fixed them on the surface of amino silicon carbide to form a thermally conductive filler.

[0027] Among them, the reducing agent sodium hypophosphite converts Co 2+ The chemical equation for reduction to cobalt atoms is as follows:

[0028] Co 2+ +H2PO2 - +3OH - →Co+HPO3 2- +2H2O

[0029] The thermal conductive filler prepared by the present invention is cobalt loaded on the surface of amino silicon carbide, that is, the cobalt atoms play a bridge role between SiC particles, connecting adjacent SiC particles through chemical bonds or physical adsorption to form a more compact network structure. This structure not only enhances the overall stability of the filler, but also promotes the effective transfer of heat between SiC particles, thereby improving thermal conductivity.

[0030] Cobalt itself has magnetism. Adding magnetic cobalt to the thermal conductive filler prepared by the present invention can guide these thermal conductive fillers to form oriented thermal conductive channels in the PET matrix. These channels are like "highways" for heat flow, which significantly improve the heat conduction efficiency, thereby meeting the special requirements of high-performance PET composite materials for thermal conductivity.

[0031] Therefore, the invention adds the prepared silicon carbide-cobalt thermal conductive filler into PET to significantly improve its thermal conductivity, so that the PET composite material can be used in fields with high thermal conductivity requirements such as automobiles and home appliances, and has excellent application prospects. DETAILED DESCRIPTION

[0032] For ease of understanding of the present invention, the present invention will be described more fully below in conjunction with specific embodiments. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thoroughly understood.

[0033] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.

[0034] The specific information of the raw materials used in the following examples and comparative examples is as follows:

[0035] PET, brand 008L, produced by Aclo, Canada;

[0036] Urea, Shandong Jinao Chemical Co., Ltd.;

[0037] Ethanol, Yangzhou Beier New Environment Technology Co., Ltd.;

[0038] Sodium hypophosphite, Jinan Shengda Chemical Co., Ltd.;

[0039] Isopropyl alcohol, Foshan Huaxisheng Chemical Co., Ltd.;

[0040] Sodium hydroxide, Jinan Kunfeng Chemical Co., Ltd.;

[0041] Cobalt nitrate, Jinan Jiaxu Chemical Technology Co., Ltd.;

[0042] Deionized water, Jinan Hairuibao Chemical Co., Ltd.;

[0043] Antioxidant (model Irganox168, Irganox1010, Irganox1330), BASF, Germany.

[0044] It is to be understood that the above raw materials and reagents are only examples of some specific embodiments of the present invention, so that the technical solution of the present invention is clearer, and it does not mean that the present invention can only use the above reagents, and the specific scope in the claims shall prevail. In addition, the "parts" described in the examples and comparative examples, unless otherwise specified, refer to parts by weight.

[0045] Any range described in the present invention includes the end value and any numerical value between the end values ​​and any sub-range formed by the end value or any numerical value between the end values.

[0046] Preparation Example 1

[0047] (1) 300 g of silicon carbide, 200 g of urea, 800 g of isopropanol, and 900 g of deionized water were mixed, added to a ball mill, and ball-milled for 10 h to obtain a mixture, and the mixture was filtered, washed, and dried in an oven at 60° C. for 4 h to obtain modified silicon carbide with amino groups on the surface;

[0048] (2) 300 g of modified silicon carbide, 100 g of sodium hypophosphite, 200 g of sodium hydroxide, 800 g of ethanol, 260 g of cobalt nitrate, and 900 g of deionized water were added to a flask, and reacted in a 50° C. water bath for 8 h. The reactants were filtered and washed, and then dried in an oven at 50° C. for 4 h to obtain silicon carbide-cobalt thermal conductive filler M1.

[0049] The rotation speed of the ball mill is 200 r / min.

[0050] Example 1

[0051] Weigh 84 parts of PET, 10 parts of thermal conductive filler M1, and 0.1 parts of antioxidant 1010, mix and stir evenly to obtain a mixture;

[0052] The mixed material is put into a twin-screw extruder for extrusion and granulation to obtain a thermal conductive PET composite material P1.

[0053] Wherein, the twin-screw extruder includes six temperature zones arranged in sequence, with the temperature of zone one at 240°C, the temperature of zone two at 280°C, the temperature of zone three at 280°C, the temperature of zone four at 280°C, the temperature of zone five at 280°C, the temperature of zone six at 280°C, the head temperature at 280°C, and the screw speed at 200r / min.

[0054] Preparation Example 2

[0055] (1) 400 g of silicon carbide, 240 g of urea, 900 g of isopropanol, and 1.0 kg of deionized water were mixed, added to a ball mill, and ball milled for 12 h to obtain a mixture. The mixture was filtered, washed, and dried in an oven at 70° C. for 8 h to obtain modified silicon carbide with amino groups on the surface.

[0056] (2) 400 g of modified silicon carbide, 120 g of sodium hypophosphite, 240 g of sodium hydroxide, 900 g of ethanol, 300 g of cobalt nitrate, and 1.0 kg of deionized water were added to a flask, and reacted in a 60° C. water bath for 14 h. The reactants were filtered and washed, and then dried in an oven at 70° C. for 6 h to obtain silicon carbide-cobalt thermal conductive filler M2.

[0057] The rotation speed of the ball mill is 280r / min.

[0058] Example 2

[0059] Weigh 104 parts of PET, 16 parts of thermal conductive filler M2, 0.1 parts of antioxidant 1010, 0.2 parts of antioxidant 168, and 0.2 parts of antioxidant 1330, mix and stir evenly to obtain a mixture;

[0060] The mixed material is put into a twin-screw extruder for extrusion and granulation to obtain a thermal conductive PET composite material P2.

[0061] Wherein, the twin-screw extruder includes six temperature zones arranged in sequence, with the temperature of zone one at 260°C, the temperature of zone two at 300°C, the temperature of zone three at 300°C, the temperature of zone four at 300°C, the temperature of zone five at 300°C, the temperature of zone six at 300°C, the head temperature at 300°C, and the screw speed at 280r / min.

[0062] Preparation Example 3

[0063] (1) 350 g of silicon carbide, 220 g of urea, 850 g of ethanol, and 950 g of deionized water were mixed and added to a ball mill for 11 h to obtain a mixture. The mixture was filtered, washed, and dried in an oven at 65° C. for 6 h to obtain modified silicon carbide with amino groups on the surface.

[0064] (2) 350 g of modified silicon carbide, 110 g of sodium hypophosphite, 220 g of potassium hydroxide, 850 g of isopropanol, 280 g of cobalt nitrate, and 950 g of deionized water were added to a flask and reacted in a 55°C water bath for 11 h. The reactants were filtered and washed, and then dried in an oven at 60°C for 5 h to obtain silicon carbide-cobalt thermal conductive filler M3.

[0065] The rotation speed of the ball mill is 240r / min.

[0066] Example 3

[0067] Weigh 94 parts of PET, 13 parts of thermal conductive filler M3, 0.1 parts of antioxidant 168, and 0.2 parts of antioxidant 1010, mix and stir evenly to obtain a mixture;

[0068] The mixed material is put into a twin-screw extruder for extrusion and granulation to obtain a thermal conductive PET composite material P3.

[0069] Wherein, the twin-screw extruder includes six temperature zones arranged in sequence, with the temperature of zone one at 250°C, the temperature of zone two at 290°C, the temperature of zone three at 290°C, the temperature of zone four at 290°C, the temperature of zone five at 290°C, the temperature of zone six at 290°C, the head temperature at 290°C, and the screw speed at 240r / min.

[0070] Preparation Example 4

[0071] (1) 333 g of silicon carbide, 238 g of urea, 865 g of propanol, and 935 g of deionized water were mixed and added to a ball mill for 11.5 h to obtain a mixture, which was filtered, washed, and dried in an oven at 68° C. for 5 h to obtain modified silicon carbide with amino groups on its surface.

[0072] (2) Add 365 g of modified silicon carbide, 115 g of sodium hypophosphite, 238 g of sodium hydroxide, 845 g of propylene glycol, 295 g of cobalt nitrate, and 985 g of deionized water into a flask, and react in a 59°C water bath for 13 h. Filter and wash the reactants, and dry them in an oven at 62°C for 5.5 h to obtain silicon carbide-cobalt thermal conductive filler M4.

[0073] The rotation speed of the ball mill is 255r / min.

[0074] Example 4

[0075] Weigh 85 parts of PET, 15 parts of thermal conductive filler M4, and 0.1 parts of antioxidant 1010, mix and stir evenly to obtain a mixture;

[0076] The mixed material is put into a twin-screw extruder for extrusion and granulation to obtain a thermal conductive PET composite material P4.

[0077] Wherein, the twin-screw extruder includes six temperature zones arranged in sequence, with the temperature of zone one at 245°C, the temperature of zone two at 285°C, the temperature of zone three at 285°C, the temperature of zone four at 285°C, the temperature of zone five at 285°C, the temperature of zone six at 285°C, the head temperature at 285°C, and the screw speed at 255r / min.

[0078] Preparation Example 5

[0079] (1) 388 g of silicon carbide, 222 g of urea, 877 g of isopropanol, and 968 g of deionized water were mixed and added to a ball mill for 10 h to obtain a mixture. The mixture was filtered, washed, and dried in an oven at 62° C. for 6.5 h to obtain modified silicon carbide with amino groups on its surface.

[0080] (2) 309 g of modified silicon carbide, 118 g of sodium hypophosphite, 231 g of sodium hydroxide, 866 g of ethanol, 291 g of cobalt nitrate, and 935 g of deionized water were added to a flask and reacted in a 58°C water bath for 11.5 h. The reactants were filtered and washed, and then dried in an oven at 66°C for 5.5 h to obtain silicon carbide-cobalt thermal conductive filler M5.

[0081] Example 5

[0082] Weigh 85 parts of PET, 14 parts of thermal conductive filler M5, and 0.1 parts of antioxidant 1330, mix and stir evenly to obtain a mixture;

[0083] The mixed material is put into a twin-screw extruder for extrusion and granulation to obtain the thermal conductive PET composite material P5.

[0084] Wherein, the twin-screw extruder includes six temperature zones arranged in sequence, with the temperature of zone one at 250°C, the temperature of zone two at 295°C, the temperature of zone three at 295°C, the temperature of zone four at 295°C, the temperature of zone five at 295°C, the temperature of zone six at 295°C, the head temperature at 295°C, and the screw speed at 270r / min.

[0085] Comparative Example 1

[0086] (1) Weigh 85 parts of PET and 0.1 parts of antioxidant 1330, mix and stir evenly to obtain a mixture;

[0087] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PET composite material D1.

[0088] Among them, the twin-screw extruder includes six temperature zones arranged in sequence, with the temperature of zone one at 250°C, the temperature of zone two at 295°C, the temperature of zone three at 295°C, the temperature of zone four at 295°C, the temperature of zone five at 295°C, the temperature of zone six at 295°C, the head temperature at 295°C, and the screw speed at 270r / min.

[0089] Comparative Example 2

[0090] (1) Weigh 85 parts of PET, 14 parts of silicon carbide, and 0.1 parts of antioxidant 1330, mix and stir evenly to obtain a mixture;

[0091] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PET composite material D2.

[0092] The twin-screw extruder includes six temperature zones arranged in sequence, with zone one at 250°C, zone two at 295°C, zone three at 295°C, zone four at 295°C, zone five at 295°C, zone six at 295°C, die head temperature at 295°C, and screw speed at 270r / min.

[0093] Comparative Example 3

[0094] (1) Weigh 85 parts of PET, 10 parts of silicon carbide, 4 parts of cobalt nitrate, and 0.1 parts of antioxidant 1330, mix and stir evenly to obtain a mixture;

[0095] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PET composite material D3.

[0096] The twin-screw extruder includes six temperature zones arranged in sequence, with zone one at 250°C, zone two at 295°C, zone three at 295°C, zone four at 295°C, zone five at 295°C, zone six at 295°C, die head temperature at 295°C, and screw speed at 270r / min.

[0097] The PET composite materials prepared in the above Examples 1-5 and Comparative Examples 1-3 were respectively tested for thermal conductivity, and the data are shown in Table 1 below:

[0098] Table 1

[0099] Test items Test Standards unit P1 P2 P3 P4 P5 D1 D2 D3 Thermal conductivity ASTM D5470 W / m·K 0.59 0.57 0.56 0.57 0.58 0.21 0.41 0.40

[0100] It can be seen from the above table:

[0101] The thermal conductivity of the PET composite materials P1-P5 is greater than that of the PET composite materials D1-D3, which indicates that the addition of the silicon carbide-cobalt thermal conductive filler prepared by the present invention significantly improves the thermal conductivity of the PET composite materials. Although silicon carbide and cobalt nitrate are added at the same time in Comparative Example 3, the silicon carbide-cobalt thermal conductive filler in the present application cannot be formed, and the thermal conductivity of the PET composite materials cannot be improved.

[0102] Although this specification is described according to implementation modes, not every implementation mode includes only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

[0103] Therefore, the above description is only a preferred embodiment of the present application and is not intended to limit the scope of implementation of the present application; that is, all equivalent changes made according to the scope of the claims of the present application are within the protection scope of the claims of the present application.

Claims

1. A method for preparing a silicon carbide-cobalt thermal conductive filler, characterized in that: The following steps are involved: (1) adding silicon carbide and urea to an organic solvent, mixing them, and then ball milling the mixture to obtain a mixture, filtering, washing, and drying the mixture to obtain modified silicon carbide with amino groups on its surface; (2) Adding modified silicon carbide, sodium hypophosphite and cobalt nitrate into an alkaline solution, reacting in a water bath, filtering, washing and drying to obtain a silicon carbide-cobalt thermal conductive filler.

2. The preparation method according to claim 1, characterized in that: In step (1), the mass ratio of silicon carbide to urea is (30-40):(20-24).

3. The preparation method according to claim 1, characterized in that: In step (1), the organic solvent is an aqueous solution of isopropanol, ethanol, propanol, acetone or dimethylformamide; In step (2), the alkaline solution is composed of a base and an organic solvent, wherein the base is sodium hydroxide or potassium hydroxide, and the organic solvent is an aqueous solution of ethanol, isopropanol or glycerol.

4. The preparation method according to claim 1, characterized in that: In step (1), the rotation speed of the ball mill is 200-280 r / min and the time is 10-12 h.

5. The preparation method according to claim 1, characterized in that: In step (2), the mass ratio of the modified silicon carbide, sodium hypophosphite and cobalt nitrate is (30-40): (10-12): (26-30).

6. The preparation method according to claim 1, characterized in that: In step (2), the temperature of the water bath reaction is 50-60° C. and the time is 8-14 h.

7. A silicon carbide-cobalt thermal conductive filler prepared by the preparation method according to any one of claims 1 to 6.

8. A thermally conductive PET composite material, characterized in that: It is prepared from the following components in parts by weight: PET 84-104 parts Thermally conductive filler 10-16 parts Antioxidant 0.1-0.5 parts The thermally conductive filler is the silicon carbide-cobalt thermally conductive filler as claimed in claim 7.

9. A thermally conductive PET composite material according to claim 8, characterized in that: The antioxidant is at least one of antioxidant 168, antioxidant 1010, and antioxidant 1330.

10. A method for preparing a thermally conductive PET composite material according to claim 8 or 9, characterized in that: The method comprises the following steps: weighing PET, thermal conductive filler and antioxidant according to weight, mixing and stirring evenly to obtain a mixture; then adding the mixture into a twin-screw extruder, extruding and granulating to obtain a thermal conductive PET composite material.